Baby shoes to crochet Fashion styles for little feet - Frthmann, Lucia (kent, England Search Press, 2016)
16 cute crocheted baby shoe designs modelled on grown-up shoes
For Little Ladies: Ballerinas, Peep-toes, Ankle-strap ballerinas, Mary Janes, Lace Shoes, Sandals with Straps, Wild Thing!: Cowboy Boots, Hippy Boots, Fur Boots, Sporty & Cheeky: Gym Shoes, Basketball Shoes, Hiking Boots, Summer, Sun and Sandal Mood: Garden Shoes, Flips Flops, Espadrilles, Wedge Sandal
1 2 13
Keywords: Children's shoes; Crocheting -- Patterns; Infants' clothing